The Management of the Cerebellar Hematoma after Posterior Cranial Fossa Trauma: A Case Report and Literature Review: Management of the Cerebellar Hematoma after Posterior Cranial Fossa Trauma - Encarnacion-Santos, Daniel; Axenova, Marina; Subhiddinovich, Kamolov Mehriddin; Chmutin, Gennady; Chmutin, Egor (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2026)
Abstract Background:Traumatic cerebellar hematomas are also known as hemorrhagic contusions and are less frequent than those of non-traumatic origin. The anatomical complexity of this area can be incalculable or disastrous; they can be isolated hemorrhages, solitary, or associated with a subdural hematoma. Cerebellar hematomas can be acute or delayed, the latter sometimes being termed a delayed traumatic intracerebellar hematoma. Case Description A 76-year-old woman presented to the emergency department several hours after being found unconscious. On initial examination, she had an occipital abrasion without fracture. Her Glasgow Coma Scale (GCS) score was 7 (E4, V4, M6), with asymmetrical but reactive pupils suggestive of focal neurologic deficits. During her physical examination show, Motor strength was 3/5 to the left, and there were no cranial nerve impairments. a CT scan was done, and we observe a left cortical stroke with hemorrhage and right hemiparesis (motor strength 4/5). Conclusion After performing a suboccipital craniotomy with the aim of evacuating the hematoma from the posterior cranial fossa that compressed the cerebellar anatomical structures, which previously caused the right hemiparesis, an emergency confirmation and treatment were greatly facilitated by CT imaging, underscoring its importance in managing posterior fossa trauma.